2017
DOI: 10.18769/ijasos.366855
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being of Volunteer Teacher Trainers in the Remote Area in Indonesia

Abstract: Indonesia is a wide country and it consists of thousands of islands. This condition makes many regions in Indonesia do not get the proper educational facilities. In addition, the quality of teachers in the remote areas is still poor. People who concern with the condition of education in the remote areas are still rare because of the limited access and high cost to get there. However, there is one group of volunteers who care about the condition of education in the remote areas of Indonesia called RUBI (Ruang B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Also, intrinsic motivation correlates positively significantly with well-being. Akhtar (2017) mentioned advantages perceived as volunteers such as developing personal competence, increasing insight and knowledge, gaining inner satisfaction, expanding social relations and becoming more grateful. Recently, researchers found that Being a volunteer had a positive effect on individual mental health and well-being (Whillans et al, 2017;Tabassum, Mohan, Smith, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Also, intrinsic motivation correlates positively significantly with well-being. Akhtar (2017) mentioned advantages perceived as volunteers such as developing personal competence, increasing insight and knowledge, gaining inner satisfaction, expanding social relations and becoming more grateful. Recently, researchers found that Being a volunteer had a positive effect on individual mental health and well-being (Whillans et al, 2017;Tabassum, Mohan, Smith, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Handian et al (2017) juga melaporkan perasaan bahagia pada relawan ketika mereka berbagi dengan anak yang mengidap kanker. Akhtar (2017) juga mengkaji kebahagiaan relawan dalam menjalankan tugasnya dan melaporkan bahwa di antara dampak yang dialami relawan adalah menjadi lebih positif dan bersyukur atas hidupnya. Nuryanti (2020) juga melaporkan bahwa rasa bahagia adalah salah satu dampak positif yang dialami para relawan ketika menjalankan tanggung jawabnya.…”
unclassified